اسلامی کریڈٹ کارڈ کے تورق ماڈل کا فقہی جائزہ: TAWARRUQ MODEL OF ISLAMIC CREDIT CARD: A JURISTPRUDENTIAL ANALYSIS (Zia e Tahqeeq, 2025)
Islamic finance has gained prominence in the global finance landscape as an alternative to conventional banking systems. The emergence of Islamic finance has led to the development of financial products designed to adhere to sharī‘ah principles and one such product is the Islamic credit card. Recently few Islamic banks especially in Malaysia produced Islamic credit card based on Tawarruq model the same has adopted by Faysal Islamic bank in Pakistan. The paper presents a jurisprudential analysis of Islamic credit cards, aiming to provide a comprehensive understanding of their legal and ethical foundations. This study discusses the fundamental concepts of Islamic credit cards, including the prohibition of conventional credit cards and introduction of Tawarruq and it’s models for credit crads. It investigates the two basic models of Tawarruq used by Islamic credit cards providers to ensure compliance with sharī‘ah. This analysis seeks to contribute in the field of Islamic finance by providing a history of credit cards, operational aspects and regularity implications. In conclusion, this study aims to promote a deeper understanding of their role in facilitating financial transactions in accordance with sharī‘ah compliance, ultimately serving as a valuable resource for scholars and policymakers in the field of Islamic finance.